Organisasi dan Mekanisme Kerja Pengawasan Pendidikan - Willem Mantja (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
When a plan is being implemented, its organizational structure is then established. Though the existence of the structure cannot guarantee the success of the plan, it facilitates the realization of the goal so that the members of the organization can be led and motivated. Control function holds a very important role as it serves as an ultimate link of the function of educational management. Therefore, the value of controlling lies on its relationship with planning and activities delegated to the members.